Using ELSA Speak for EFL Student’s Pronunciation: A Literature Review - Yuliana, Ayu Miranti (IKIP Siliwangi, 2025)
Pronunciation is an essential part of the field of communication. However, it can be challenging for English as a Foreign Language (EFL) students to pronounce confidently due to several pronunciation problems. To respond to these problems, the researcher aimed to explore EFL students' perspectives on the impact of using ELSA Speak. The researcher first conducted a literature review analysis by observing fifteen articles published in national and international journals. Then, five participants who had taken an Academic Speaking class in batch 2021 or 2022 were interviewed to discuss the results of the literature review analysis and explored participants' personal experiences using ELSA Speak. The data was qualitatively examined and presented as themes. The results showed positive perspectives from the participants when using ELSA Speak, which highlighted four themes included in the findings. At the end of the paper, the researcher presented practical recommendations for the teacher and future researchers regarding using ELSA Speak to learn pronunciation.